Roller massage does not alter evoked pain perception or contractile properties - Doeweling, A.; Cavanaugh, M. T.; Hogdson, D. D.; Quigley, P. J.; Whitten, J. H.; Young, J. D.; Behm, D. G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Foam-rolling (FR) and roller massage (RM) have become a common practice with warm-up or recovery from exercise. It is believed to promote soft-tissue extensibility, improve muscle function, and reduce pain. However, it is not known if RM directly alters muscle properties. Therefore, the aim of this study was to determine if RM has an immediate effect on evoked contractile properties and sensation of evoked pain. Methods: In a randomized repeated-measures design (n = 12) the acute effects of three different RM interventions on evoked pain perception (PP / i.e. pain visual analog scale (VAS) with evoked twitch and submaximal and maximal tetanic stimulation of the dominant calf muscles), maximum voluntary isometric contraction (MVIC) force and evoked contractile properties (twitch and tetanic maximum force, time to peak force, half relaxation time and rate of force development) were investigated. The interventions consisted of 3 x 30s bouts of 1) heavy rolling massage (7/10 perceived pain) on the stimulated calf, 2) heavy rolling massage (7/10) on the contralateral limb and 3) light rolling (<1/10) on the stimulated calf (Control). Testing was conducted prior to the RM intervention as well as 1 and 5 min after the intervention, respectively. Results: A two-way repeated measures ANOVA revealed no statistically significant main effects or interactions (roller massage intervention x testing) regarding PP, MVIC and evoked contractile properties. Discussion: This data suggests that a single bout of RM had no effect on evoked or voluntary contractile properties. Furthermore, evoked twitch and tetanic pain remained unaffected by RM. Based on the present and prior research; RM may not predominately affect muscle properties nor reduce all types of pain.